Metal accumulation and oxidative stress biomarkers in octopus (Octopus vulgaris) from Northwest Atlantic - Semedo, Miguel (2012)
Metals are ubiquitous in the environment and accumulate in aquatic organisms and are known for their ability to enhance the production of reactive oxygen species (ROS). In aquatic species, oxidative stress mechanisms have been studied by measuring antioxidant enzyme activities and oxidative damages in tissues. The aim of this study was to apply and validate a set of oxidative stress biomarkers and correlate responses with metal contents in tissues of common octopus (Octopus vulgaris). Antioxidant enzyme activity (catalase — CAT, superoxide dismutase — SOD and glutathione S-transferases — GST), oxidative damages (lipid peroxidation — LPO and protein carbonyl content — PCO) andmetal content (Cu, Zn, Pb, Cd and As) in the digestive gland and armof octopus, collected in the NWPortuguese coast in different periods, were assessed after capture and after 14 days in captivity. CAT and SOD activitieswere highly responsive to fluctuations inmetal concentrations and able to reduce oxidative damage, LPO and PCO in the digestive gland. CAT activity was also positively correlated with SOD and GST activities, which emphasizes that the three enzymes respond in a coordinated way to metal induced oxidative stress. Our results validate the use of oxidative stress biomarkers to assess metal pollution effects in this ecological and commercial relevant species.Moreover, octopus seems to have the ability to control oxidative damage by triggering an antioxidant enzyme coordinated response in the digestive gland.